Simultaneous Estimation of Rofecoxib and Tizanidine Hydrochloride in Tablets by RP-HPLC - LAKSHMANA RAO*, A.; PRAVEEN VARMA, D. (Asian Journal of Chemistry, 2009)
A simple, precise, accurate and rapid RP-HPLC method has been developed and validated for the simultaneous estimation of rofecoxib and tizanidine hydrochloride in pharmaceutical dosage forms. The process was carried out on C18 column (250 × 4.6 mm ID, particle size 5 μm) using a mobile phase of phosphate buffer pH 3.0, acetonitrile and methanol in the ratio of 60:30:10 v/v/v at a flow rate of 1.0 mL/min. The detection of rofecoxib and tizanidine hydrochloride was carried out at a wave length of 274 nm. The calibration curves were linear over the range of 50- 250 μg/mL of rofecoxib and 4-20 μg/mL of tizanidine hydrochloride. The retention time of rofecoxib and tizanidine hydrochloride was found to be 4.69 and 2.41 min, respectively. Results of the analysis were validated statistically by recovery studies. The proposed method is simple, rapid and sensitive. It can be successfully used to estimate the drug contents of marketed formulations.